Electronic Payment Threats and Security: A Systematic Literature Review - Erik Iman Heri Ujianto; Amelia Citra Dewi; Rianto, Rianto (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
In the emerging field of electronic payment systems, security challenges have become a major concern. This research addresses a comprehensive understanding of mitigation strategies for these threats. Through systematic literature analysis, we investigated the security vulnerabilities in electronic payment processes and discovered the latest blockchain technology as a strengthened security framework. Our findings reveal that while encryption and authentication provide the foundation of security, the integration of blockchain technology offers an unprecedented level of transaction integrity and transparency. This research not only highlights the urgent need for electronic payment security measures but also highlights the potential of blockchain and machine learning as transformative solutions. The implications of our research indicate an important shift in payment systems towards more secure and resilient electronic systems, paving the way for future research to explore the integration of cutting-edge technologies in combating ever-evolving cyber threats by leveraging blockchain technology, quantum computing and machine learning.